ANALISIS RASIO LIKUIDITAS DAN RASIO AKTIVITAS DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA BPJS KETENAGAKERJAAN CABANG MEDAN KOTA - Remi Syahdeni; Ardhansyah Putra Hrp (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2021)
This study aims to see the profit growth in BPJS Ketenagakerjaan Branch Medan Kota. This type of research is descriptive qualitative, the data collection technique used is documentation, the data used are financial reports (Activity Reports and Financial Position Reports) for the last 5 (five) years from 2015 to 2019 using the financial ratio analysis method. The financial ratios used are the Liquidity Ratio (Working Capital to Total Asset) and the Activity Ratio (Total Asset Turnover). The results showed that the Liquidity Ratio has a good performance value in profit growth because the amount of current assets is higher than current debt and the value of theratio Working Capital to Total Asset is above industry standards. And the activity ratio has a poor financial performance value in profit growth because theratio Total Asset Turnover during 2015 to 2019 has a value that is below industry standards.